Effects of the Income Stabilization Tool on farm income level, variability and concentration in Italian agriculture - Simone Severini; Giuliano Di Tommaso; Robert Finger (Agricultural and Food Economics, 2019)
This paper provides an ex ante assessment of the effects of the Income Stabilization Tool (IST), a new risk management tool proposed in the Common Agricultural Policy of the European Union. We investigate the effects of IST on income variability and levels as well as on income inequality in the farming population. We take Italian agriculture as an example as the introduction of IST is currently under discussion there. A rich panel of 2777 farms was studied over a period of 7 years. We use stochastic simulation to derive different income inequality estimates and apply Gini decomposition approaches to assess the distributional implications of IST. We compare the current income situation with that resulting from a hypothetical implementation of IST under different policy scenarios, also accounting for reduced levels of CAP direct payments. We find that IST not only stabilizes farm income but also enhances its level and reduces income inequality in Italian agriculture. IST is more effective in reducing income inequality when farmers pay contributions to mutual funds that are proportional to their income compared to the case of flat rate contributions. Finally, results do not support the hypothesis that the impact of IST will differ if the level of direct payments were to be reduced. Thus, results seem robust enough to accommodate future policy conditions.
Keywords: D63; G22; Q12; Q18; 330; Agricultural policy; Income inequality; Income Stabilization Tool; Direct payments; Risk management